Proceedings of the 33rd International Symposium on Lattice Field Theory — PoS(LATTICE 2015) 2016
DOI: 10.22323/1.251.0001
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on chiral symmetry breaking in QCD

Abstract: I review recent progress achieved on the lattice in the quantitative comprehension of chiral symmetry breaking in QCD. Emphasis is given to the recent precise computations of the spectral density of the Dirac operator in the continuum limit, and of the topological susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…We found that cut-off effects in the topological susceptibility from the GF are much larger than in the susceptibility from spectral projectors and can be up to 500% at the coarsest lattice spacing of around 0.09 fm. Nevertheless, the continuum limit is always compatible between GF and spectral projectors, and also independent of the flow time (GF) or the renormalized spectral threshold (spectral projectors), as long as these scales are fixed in physical units [93]. We refer the reader to this paper for more details.…”
Section: Discussionmentioning
confidence: 99%
“…We found that cut-off effects in the topological susceptibility from the GF are much larger than in the susceptibility from spectral projectors and can be up to 500% at the coarsest lattice spacing of around 0.09 fm. Nevertheless, the continuum limit is always compatible between GF and spectral projectors, and also independent of the flow time (GF) or the renormalized spectral threshold (spectral projectors), as long as these scales are fixed in physical units [93]. We refer the reader to this paper for more details.…”
Section: Discussionmentioning
confidence: 99%
“…[35,36] and for the standard Wilson gluonic action and the non-perturbatively O(a)-improved Wilson fermion action [37] by Refs. [38][39][40]. As an example for the determination of the chiral condensate on the lattice we follow the discussion in Ref.…”
mentioning
confidence: 99%
“…Therefore, the following results, see also Refs. [31,[38][39][40][41], can be computed using the (improved) Wilson formulation of lattice QCD even though the latter violates chiral symmetry at energies on the order of the inverse lattice spacing. We conclude that the mode number ν is a renormalization group invariant quantity…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…see for example [64,65,66] for reviews. The symmetry properties of the QCD Lagrangian become more apparent when rewriting it in terms of left-and right-handed fields, which gives…”
Section: Qcd Phase Diagram and Symmetriesmentioning
confidence: 99%